Feasibility of hemoperfusion using extracorporeal therapy in the horse - Hobbs, Kallie J.; Le Sueur, Andre N. V.; Burke, Megan J.; Cooper, Bethanie L.; Sheats, M. Katie; Ueda, Yu (Frontiers in Veterinary Science, 2024)
Objective Develop, implement, and monitor for adverse effects of, a novel hemoperfusion therapy in adult horses. Methods A prospective, observational feasibility study using three healthy adult horses from the North Carolina State University teaching herd. Health status was determined by physical exam, complete blood count, coagulation panel, and serum biochemistry. Each horse was instrumented with a 14 Fr × 25 cm double-lumen temporary hemodialysis catheter and underwent a 240 min polymer-based hemoperfusion session. Horses were administered unfractionated heparin to maintain anti-coagulation during the session. Given the novelty of this therapy in horses, each horse was treated as a learning opportunity that informed an iterative process of protocol development and modification. Measurements and main results Our long-term goal is to investigate potential clinical applications of hemoperfusion in horses, including cytokine reduction in horses with severe SIRS/sepsis. Horses were monitored for changes in clinical exam, biochemistry and hematology parameters. Additionally, cytokines were quantified to determine whether extracorporeal hemadsorption therapy alone caused an inflammatory response. Our results show that hemoperfusion therapy was associated with decreased platelet counts and serum albumin concentration. There was no significant change in plasma cytokine concentrations with hemoperfusion therapy. In one horse, the cytokine concentrations decreased, as previously reported with hemoperfusion therapy in humans. Hypothesis We hypothesized that hemoperfusion therapy could be performed in healthy adult horses without significant adverse effects. Conclusion Polymer-based hemoperfusion is a feasible extracorporeal therapy (ECT) modality for adult horses. Additional studies are needed to further establish clinical protocols, as well as establish efficacy of polymer-based hemoperfusion for treatment of various conditions in horses, including intoxications, immune-mediated conditions, and sepsis.